BiBibliometric Trends of Environmental-STREAM in Science Education - Tri Wahyu Agustina; Evi Roviati; Jamiludin Hidayat; Ade Yeti Nuryantini; Fitri Hayati Kurnia; Lia Lia; Putri Lestari (Universitas Muhammadiyah Purworejo, 2026)
The integration of environmental issues and religious aspects in science learning is essential to foster student responsibility holistically. The development of the integration of these issues has not been well mapped. This study presents a bibliometric analysis to eval_uate the global publication trends of Environmental-STEM, STEAM, and STREAM in science education. The Publish or Perish application is used as a source for the Google Scholar database as well as VOSviewer for keyword mapping (co-word analysis), a comprehensive screening of 499 articles in the 2015–2025 range. Based on the strict PRISMA protocol, 125 articles were obtained that met the final eligibility criteria for analysis. The results of the analysis show that interdisciplinary publications had soared in 2020. Research that explicitly integrates environmental aspects as well as religious aspects in the framework of STREAM called Environmental-STREAM (E-STREAM) has not been found in network visualization. This crucial research gap confirms the novelty of this study which emphasizes the urgency of E-STREAM as a distinctive aspect-based learning framework. Practically, this research contributes in the form of a conceptual roadmap for educators and curriculum developers to design contextual science learning that bridges science literacy, creativity, and environmental responsibility rooted in the spiritual-ethical side.